2021
DOI: 10.1136/bmjopen-2020-042362
|View full text |Cite
|
Sign up to set email alerts
|

Strategies used by emergency care professionals to handle interpersonal difficulties with patients: a qualitative study

Abstract: ObjectivesIdentify the strategies implemented by emergency care professionals when facing tension and interpersonal violence from patients and their friends and family.DesignDescriptive qualitative study based on 38 semidirective interviews.ParticipantsDoctors, nurses, nursing assistants and administrative staff.SettingFour emergency departments (EDs) from three French university hospitals.ResultsAccording to the medical professionals interviewed, the difficulties that they encounter with patients or their acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…Those interventions were, for instance, explaining ED processes to impatient patients and their attendants, flight in case of physical encounter, or asking for help from experienced colleagues. Such personal strategies, which employees learn and implement on their own, have also been described in a previous study conducted by Charrier et al [ 21 ], e.g., communication strategies aiming at a reciprocal understanding with the patient to keep the interaction congenial. These measures were commonly applied by participants of the current study as well and one reason that was addressed was that these strategies were not dependent on financial resources and could be implemented without organisational efforts.…”
Section: Discussionmentioning
confidence: 72%
“…Those interventions were, for instance, explaining ED processes to impatient patients and their attendants, flight in case of physical encounter, or asking for help from experienced colleagues. Such personal strategies, which employees learn and implement on their own, have also been described in a previous study conducted by Charrier et al [ 21 ], e.g., communication strategies aiming at a reciprocal understanding with the patient to keep the interaction congenial. These measures were commonly applied by participants of the current study as well and one reason that was addressed was that these strategies were not dependent on financial resources and could be implemented without organisational efforts.…”
Section: Discussionmentioning
confidence: 72%
“…Hosseinpour-Dalenjan et al (2019) showed that there is a high correlation between nurses' work engagement and patient or visitor incivility [ 26 ]. Charrier et al (2021) showed that nurses in the emergency department face lack of civility and deviant behaviors with patients and their accompanying family members, which requires strategies to manage the interpersonal difficulties [ 30 ]. An Iranian study showed that the incivility of physicians in the nursing workplace was the highest and the incivility of supervisors was the lowest [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This multifaceted context exacerbates the unique and demanding nature of nursing practice within EDs (Parvaresh‐Masoud et al., 2021). Conflict in the context of EDs is a prominent feature in nursing practice due to the complexity and stressful environment in which ED nurses provide care (Charrier et al., 2021). It can also increase the margin of error in the ED, which jeopardizes the safety and quality of rendered care (Labrague et al., 2018).…”
Section: Introductionmentioning
confidence: 99%